On the Behavior of Algebraic Polynomial in Unbounded Regions with Piecewise Dini-Smooth Boundary
Let G ⊂ ℂ be a finite region bounded by a Jordan curve L := ∂G, let \( Ω :=extG \) (with respect to \( C \) ), let Δ := w : |w| > 1, and let w = Φ(z) be the univalent conformal mapping of Ω onto Δ normalized by Φ (∞) = ∞, Φ′(∞) > 0. Also let h(z) be a weight function and let A p (h,G), p > 0 denote a class of functions f analytic in G and satisfying the condition f_A_p(h,G)^p:=Gh(z)|f(z)|^pdσ_z0 \) , for Jacobi-type weight function in regions with piecewise Dini-smooth boundary., number=5, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Abdullayev, F. G. and Özkartepe, P., year=2014, month=May, pages=579–597